Pengaruh Pemberian Pendidikan Kesehatan Tentang OHO Terhadap Tingkat Pengetahuan Pasien DM Tentang OHO - Yuliska Isdayanti (Poltekkes Kemenkes Surakarta, 2018)
Background: The purpose of this research was to determine the effect of health education about Oral Hypoglycemic Drugs on the knowledge level of patient DM about Oral Hypoglycemic Drugs. Method: Using pre-experimental with one group pretest-posttest design. The sample used is a diabetes mellitus patients who consumed Oral Hypoglycemic Drugs in Persadia units RSUD Dr.Moewardi in Surakarta as much as 30 respondents. Assessment of the knowledge level diabetes mellitus patients about Oral Hypoglycemic Drugs using a questionnaire. Data analysis using the Paired t-Test. The Results: Showed p=0,000 with correlation coefficient 0.558. Conclusion: Based on the results of the study, it is known that there is a significant influence between the provision of health education about OHO on the level of knowledge of DM patients about OHO.